VIABILITAS INOKULUM BAKTERI ASAM LAKTAT (BAL) YANG DIKERINGKAN SECARA KEMOREAKSI DENGAN KALSIUM OKSIDA (CaO) DAN APLIKASINYA PADA TEMPOYAK - Neti Yuliana (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
Chemoreaction drying using Calcium oxide (CaO) has potential to be applied due to its heatless effect and low cost. The aim of this research is to know the effect of CaO concentration upon chemoreaction drying on viability of lactic acid bacteria (LAB), as well as to know the effect of carboxyl methyl cellulose (CMC) as protecting agent on viability of LAB and to evaluate its application of that inoculums on fermented durian. The results showed that the higher concentration of CaO used, the faster velocity of drying. The highest viability of LAB (68%) was achieved by the treatment of CaO ratio and culture of 1:5. However, the LAB viability of this research was considered low indicated that it needs improvement in the further research. The CMC as protecting agent was able to increase viability of LAB compare to those without CMC treatment. Application of inoculums to tempoyak fermentation was comparable as it had highest sensorial score and total LAB compare to those without LAB inoculums in term of more acid. Keywords: Calcium oxide, chemoreaction, drying, tempoyak, viability.